Suppression of arthritis-induced bone erosion by a CRAC channel antagonist. Issue 1 (8th January 2016) - Blair, Harry C; Soboloff, Jonathan; Robinson, Lisa J; Tourkova, Irina L; Larrouture, Quitterie C; Witt, Michelle R; Holaskova, Ida; Schafer, Rosana; Elliott, Meenal; Hirsch, Raphael; Barnett, John B
Abstract : Objective: We have shown in vitro and in vivo that osteoclast maturation requires calcium-release activated calcium (CRAC) channels. In inflammatory arthritis, osteoclasts mediate severe and debilitating bone erosion. In the current study, we assess the value of CRAC channels as a therapeutic target to suppress bone erosion in acute inflammatory arthritis. Methods: Collagen-induced arthritis (CIA) was induced in mice. The CRAC channel inhibitor 3, 4-dichloropropionaniline (DCPA) and a placebo was administered 1 day prior to collagen II booster to induce arthritis. Effects on swelling, inflammatory cell invasion in joints, serum cytokines and bone erosion were measured. Results: Assays, by blinded observers, of arthritis severity showed that DCPA, 21 mg/kg/day, suppressed arthritis development over 3 weeks. Bone and cartilage damage in sections of animal feet was reduced approximately 50%; overall swelling of joints was reduced by a similar amount. Effects on bone density by µCT showed clear separation in DCPA-treated CIA animals from CIA without treatment, while differences between controls without CIA and CIA treated with DCPA differed by small amounts and in most cases were not statistically different. Response was not related to anticollagen titres. There were no adverse effects in the treated group on animal weight or activity, consistent with low toxicity. The effect was maximal 12–17 days after collagen booster, during the rapid appearance of arthritis in untreated CIA. At 20 days after treatment (day 40), differences in arthritis score were reduced and tumour necrosis factor α, interleukin (IL)-1, or IL-6 in the serum of the animals were similar in treated and untreated animals. Conclusions: DCPA, a novel inhibitor of CRAC channels, suppresses bone erosion associated with acute arthritis in mice and might represent a new treatment modality for acute arthrits.